Reseña - López Forero, Abel Ignacio (2014)
Davis, Kathleen. Periodization and Sovereignty. How Ideas of Feudalism and Secularization Govern the Politics of Time. Philadelphia: University of Pennsylvania Press, 2008. 187 pp.